2018
DOI: 10.1007/s12649-018-0458-8
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution and Physicochemical Properties of Pellets Made of Straw, Hay, and Their Blends

Abstract: The aims of the study were (a) the determination of the physicochemical characteristics of properties of pellets made of shredded residue from hay, wheat straw, and their blend at a ratio of 50:50, and (b) the determination of a mathematical model of pellet durability, using a response surface method. Tests were conducted according to applicable standards. As a result of thermal changes during the pressure agglomeration process, the material moisture content of pellets had slightly decreased versus raw three b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Wang et al [89] reported an increase only in mechanical characteristics by mixing wheat and rice straw, while the LHV did not improve substantially. Similar results were presented by Lisowski et al [90] in relation to hay and straw mixing-a mechanical improvement without positive effects on LHV.…”
Section: Effects Of Blending and Binders On Pellet Qualitysupporting
confidence: 90%
“…Wang et al [89] reported an increase only in mechanical characteristics by mixing wheat and rice straw, while the LHV did not improve substantially. Similar results were presented by Lisowski et al [90] in relation to hay and straw mixing-a mechanical improvement without positive effects on LHV.…”
Section: Effects Of Blending and Binders On Pellet Qualitysupporting
confidence: 90%
“…The high density of the agglomerate could be related to the high specific density of the raw material. Our experience indicates that walnut shells with high specific density, the milled particles of which were characterised by high sphericity, had poor bonds and the pellets were characterised by low strength [ 33 ] compared to the pellets made of fibrous biomass with low specific density, yet more durable bindings [ 20 ]. Therefore, in the next section, the strength parameters of pellets subjected to compressive load are analysed.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of fine particles in the mixture should not exceed 10–20%, as the quality of the feed pellets decreases and the fine particles increase the friction against the die [ 19 ] if this amount is exceeded. The addition of hay to straw with longer particles increased the homogeneity of the blend and pellet strength [ 20 ], as the longer and wider straw particles wrap the small particles and form a “solid bridge” [ 21 ]. The compaction pressure and particle size significantly influence the density of the logging residues [ 22 ], corn, and switchgrass barley straw pellets; however, the different particle sizes of the WS did not have a significant influence on the pellet density [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Austrian and German Standards, 4-10 mm; Swedish standard, <25 mm; Italian Standard, 6-10 mm (depending on pellet category) while the recently developed European (EN ISO 17225-2) and International (ISO 17225-6) Standards, 6-12 mm and 6-25 mm, respectively [15]. Densi ed biomass in pellet form provides numerous advantages, among others, improved solid fuel properties, better combustion e ciency, ease of handling, storage and logistic [16].…”
Section: Introductionmentioning
confidence: 99%